La canción como recurso didáctico innovador para la enseñanza de la lengua y literatura a los estudiantes de 9no. grado de educación general básica del colegio nacional Nueve de Octubre, sección vespertina, del cantón Machala, en el período lectivo 2014 – 2015 - Guamán Lojano, Rocío del Pilar (2014)
The teaching resources strengthen the teaching-learning process, contribute and motivate learners to clarify concepts and skills set objectively. Teachers must constantly innovate methods, techniques and procedures primarily teaching resources as these are vital because they stimulate and energize student’s classes. For this reason in the present research we considered objective "Determining the shape of Teaching and Learning of Language and Literature Ninth Grade Basic General Education Association National Joint Nueve de Octubre " evening section of the city of Machala, province of El Oro, academic year 2014 -2015, to propose a new teaching resource which can improve the learning process in the area of Language Arts. Therefore in this research offer teachers of ninth grade of basic general education language arts course, a tutorial which contains a corpus of songs that serve as a methodological tool aimed to contribute to the integral development of young through traditional and new songs, adapted to the interests , needs and social , linguistic , environmental and cultural environment. For the collection of information surveys of students, teacher’s interviews and direct observation was applied to language arts classes which facilitates the verification of hypotheses. The data were processed and analyzed thoroughly, allowing us to see the reality of the result of investigation that was used in the proposed proposal.